1986
DOI: 10.1002/ana.410190411
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexamethasone on blood‐brain barrier in the normal mouse

Abstract: Dexamethasone ameliorates cerebral edema, but its effect on normal blood-brain barrier is unknown, as is the site of action. Sixteen normal mice were given dexamethasone, 3 mg/kg intramuscularly or 2 mg/kg intravenously. One to two hours later 10 mg of horseradish peroxidase (HRP) in 0.1 ml of saline was administered intravenously and allowed to circulate for 15 minutes. Brain slices were examined by light and electron microscopy. The number of HRP-permeable arteriolar segments per brain was less in dexamethas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
3
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 41 publications
3
33
3
1
Order By: Relevance
“…Our findings -in accordance with those of others [7,22,27] -indicate that Dxm may counteract both the early and the delayed phases of the formation of vasogenic oedema in the brain, and may directly rescue nerve cells from excitotoxic cell death following its interaction with neuronal and glial GRs [1]. Previous studies have demonstrated that Dxm may significantly decrease the permeability of cerebral blood vessels to the macromolecule horseradish peroxidase in the mouse [7], and may thereby reduce cerebral oedema after brain injury. Such an action of Dxm on the BBB is also suggested following cold lesion.…”
Section: Discussionsupporting
confidence: 96%
“…Our findings -in accordance with those of others [7,22,27] -indicate that Dxm may counteract both the early and the delayed phases of the formation of vasogenic oedema in the brain, and may directly rescue nerve cells from excitotoxic cell death following its interaction with neuronal and glial GRs [1]. Previous studies have demonstrated that Dxm may significantly decrease the permeability of cerebral blood vessels to the macromolecule horseradish peroxidase in the mouse [7], and may thereby reduce cerebral oedema after brain injury. Such an action of Dxm on the BBB is also suggested following cold lesion.…”
Section: Discussionsupporting
confidence: 96%
“…Recent findings suggest that glucocorticoids may stimulate ␣ 2 M release and inhibit up-regulation of MMP-9 (18,19). This is consistent with the concept that glucocorticoids may act as repair agents following BBB failure and edema formation (20). ␣ 2 M is a tetramer of four identical 180-kDa subunits exhibiting a ␤-cysteinyl-glutamyl-thiol ester bond and inhibits the target protease by physical entrapment.…”
Section: Molecular and Cellular Proteomics 2:234 -241 2003supporting
confidence: 73%
“…It has been suggested that corticosteroids produce their anti-edema effect by reducing the permeability of tumor capillaries (Figure 2) [26,31,32]. As indicated previously, corticosteroids diffuse through the plasma membrane and bind to the cytoplasmic receptor, allowing the steroid–receptor complex to move to the nucleus where it directly affects transcription of genes and also interacts with other transcription factors, mediating nontranscriptional regulation of other signaling cascades (Figure 1) [19].…”
Section: Vasogenic Edema and Corticosteroidsmentioning
confidence: 91%